Effects of Oyster Reef Sanctuaries on Fish Abundance in Pamlico Sound - Grimes, Charlotte (My University, 2024)
The value of restoring oysters to enhance natural water filtration is well-established, but the habitat value of restored reef habitat for the estuarine fish community has been less studied. Further, while artificial reef structures in the ocean, like shipwrecks, have been shown to provide valuable feeding and breeding habitat for fish, the function of artificial reefs in estuaries are poorly studied. In estuaries, the availability of adequate shelter and feeding habitat is particularly important due to the abundance of juvenile fishes. The state of North Carolina has established 14 oyster sanctuaries within Pamlico Sound as part of its shellfish restoration efforts. These oyster sanctuaries are considered artificial reef and are established with a variety of substrates including natural oyster cultch, concrete reef balls, and rip-rap marl. Acoustic imaging sonar sampling of oyster sanctuaries in Pamlico Sound was undertaken from June of 2022 to November of 2023 with the goal of comparing fish abundance on these reefs to adjacent areas without artificial substrate. The acoustic samples were analyzed to measure fish abundance and length at 26 sample points per sanctuary, which included areas outside of the sanctuary to act as a control. Fish abundance varied by a factor of 29.16 across the eight sanctuaries that were sampled. Fish abundance observed on the reef was generally higher than in the area without reef substrate, which is consistent with the belief that these reefs provide useful habit. The fish observed within the reef were also, on average, larger than fish observed outside the reef sanctuary in the control area. Understanding the value and use of oyster sanctuaries to fish in estuarine ecosystems like Pamlico Sound would provide justification for the funding and implementation of further restoration efforts.
Keywords: oysters; oyster reef sanctuaries; artificial reef habitat; Pamlico Sound; acoustic imaging; SONAR; fish abundance